EXPERIMENTAL STUDIES TO ASSESS THE EFFECTIVENESS OF "PUMPKIN OIL WITH ZINC" AND "PUMPKIN OIL WITH VITAMIN E" - Zaynutdinov Khikmatulla Sunnatovich; Aliev Ubadulla Erkinovich; Abdijalilova Zilola Khikmatullaevna (Modern American Journals, 2025)
Pumpkin is a popular and healthy vegetable that can be used to prepare a variety of delicious dishes. Pumpkin seeds, from which extract (a concentrated powder with a light nutty flavor) and oil are obtained, also have enormous nutritional value. People have used them as medicines for many centuries. Thus, in the century before last and the last century, this product was used to treat and prevent worms. It was also used in the treatment of many infectious diseases [1].Of course, not everyone can easily eat a handful of pumpkin seeds every day. Therefore, biologically active supplements in the form of pumpkin oil or seeds will be an excellent alternative to such a product. They contain many nutrients, including vitamins, minerals, healthy dietary fiber and fats. Pumpkin seeds contain a lot of antioxidants - these are carotenoids and vitamin E. Such substances are able to neutralize free radicals, which negatively affect health, including provoking the development of malignant tumors. Free radicals are essentially highly active atoms that are too actively fixed on cellular tissues.